Poly[[tetraaquabis(μ-hydroxyacetato-κ(4) O (1),O (2):O (1),O (1′))-μ(2)-sulfato-κ(2) O:O′-dicadmium(II)] monohydrate] - Rychlewska, Urszula (International Union of Crystallography, 2009)
The title compound, {[Cd(2)(C(2)H(3)O(3))(2)(SO(4))(H(2)O)(4)]·H(2)O}(n), was obtained unintentionally in a transmetallation reaction. The crystal structure contains a two-dimensional metal–organic framework based on Cd(II)–(μ-hydroxyacetato-κ(4) O (1),O (2):O (1),O (1′))–Cd(II) zigzag chains joined together by bridging SO(4) anions. The resulting layers are shifted with respect to each other and are stacked along the c axis. Their construction is supported by hydrogen bonds between water molecules and between water molecules and carboxylate or sulfate groups. Neighbouring layers are bridged by hydrogen bonds between the hydroxyl substituent and a sulfate anion. The sulfate anion and solvent water molecule are located on twofold axes. The results demonstrate that care must be taken when preparing ethylenediaminetetraacetic acid-type complexes by transmetallation, in order to avoid precipitation of metal complexes with the α-hydroxyacetate ligand.